Evaluation of Ecological Insulation Material Manufacturing with Analytical Hierarchy Process - Balo, Figen (Gazi Univ, 2017)
Utilization of insulation materials is ever increasing recently in order to achieve energy efficiency in the building industry where significant losses occur in terms of energy savings in relation with rapid consumption of fossil resources recently. Although insulation materials provide significant value in terms of energy efficiency, negative effects exist while they are being manufactured, used, and even after they are being used. Thus, along with the technical characteristics of the insulation materials, the energy consumption during the manufacturing process and the negative effects of the materials used in their production should also be evaluated. Because one of the aims of insulation is providing conformity while using less energy and reducing emission meanwhile, thus supporting the efforts of maintaining ecological balance. In this study, negative ecological effects that occur during the manufacturing process of insulation materials being widely used in construction industry are analyzed with Analytical Hierarchy Process (AHP) which one of the multi-criteria decision making
Keywords: Insulation materials; ecology; AHP; energy; environmental impact